Emerging Issues Involved in Cross-Border Securitization - A Critical Review - Goutam, Swapneshwar; Goutam, Deepeshwar (Indian Journal of Finance, 2010)
Cross-border securitization can take place without a governing country law, or under a very lax, fully enabling, country law. Yet, market and institutional intermediation are unlikely to arise, let alone flourish, without a legal infrastructure that provides uniform, predictable, stable rules of behavior. Or in other terms, international securitization is a process in which companies raise the funds from the foreign established capital markets. Traditionally, companies raise their capital by issuing securities for equity participation in the company or through loans to the company. In such a case, the security holder has recourse to the company itself for the repayment of their debt and the same is not immune from the risk of the company being bankrupt. However, this risk is removed through securitization, where the source of repayment is separated from the company and, thus the security holder is not dependent on the company for the repayment and not threatened by the company bankruptcy.